Cardiac evaluation in patients awaiting kidney transplant-position statement of the Cardiological Society of India and Indian Society of Nephrology - Ajay Bahl; Narayan Prasad; Dhurjati Prasad Sinha; Kajal Ganguly; Sandipta Roy; Debabrata Roy; Sumit Rakshit; Dilip Kumar; Saurav Das; Dinkar Bhasin; Sree Bhushan Raju; Mayuri Trivedi; et al. (Indian Heart Journal)
Cardiovascular diseases are a major cause of death after kidney transplantation. This statement addresses preoperative cardiac decision-making and management with the aim of assessing and reducing the risk of the kidney transplant surgery. Important issues from a clinician's perspective include the basic cardiovascular workup of these patients, coronary evaluation and management of coronary artery disease, valvular heart disease and left ventricular systolic dysfunction. Recovery left ventricular function after kidney transplant is discussed. In addition, the use of cardiovascular drugs in patients with special emphasis on antiplatelets and anticoagulants in patients planned for kidney transplant is also discussed.